What makes love last? eaudiobook How to build trust and avoid betrayal. - Gottman, PhD, John M. (Tantor Media, 2012)
Dr. John Gottman, the country's preeminent researcher on marriage, is famous for his Love Lab at the University of Washington in Seattle where he deciphers the mysteries of human relationships through scientific research. His thirty-five years of exploration have earned him numerous awards, including from the National Institute of Mental Health, the American Psychological Association, and the American Association for Marriage and Family Therapy. Now, Dr. Gottman offers surprising findings and advice on the characteristic that is at the heart of all relationships: Trust. Dr. Gottman has developed a formula that precisely calculates any couple's loyalty level. The results determine a relationship's likely future, including the potential for one or both partners to stray. What Makes Love Last? shows couples how to bolster their trust level and avoid what Dr. Gottman calls the "Roach Motel for Lovers." He describes how the outcome of "sliding door moments," small pivotal points between a couple, can lead either to more emotional connection or to discontent. He suggests a new approach to handling adultery and reveals the varied and unexpected non-sexual ways that couples often betray each other. What Makes Love Last? guides couples through an empirically tested, trust-building program that will help them repair and maintain any long-term, intimate romantic relationship.